Nanosensors : physical, chemical, and biological - Khanna, Vinod Kumar, 1952- (Boca Raton, Fl. : CRC Press, 2012)
'Because many chemical, biological, and physical sensors depend on interactions occurring at the nanoscale, the impact of nanotechnology on the sensor world is significant. Addressing research areas and challenges, this book describes nanosensor development from the viewpoints of materials, device structures, and functionalities. It starts from preliminary ideas and proceeds to state-of-the-art nanosensors. The book provides readers with information on the current state of nanotechnology-enabled sensors as well as their advantages, uniqueness, and limitations. It also indicates future research directions'--
'Interesting developments have taken place in the sensor field in recent years. Nanotechnology holds a great potential for revolutionizing the sensor arena. Traditional sensors are being re-engineered and recast from the nanotechnology perspective, and new sensor designs are being introduced. Sensitivity, detection range and response time of sensors have been remarkably ameliorated by using nanotechnological methods. Faster, better, cheaper and smaller sensors are becoming available. Sensor development in the nanotechnology age, the focal theme of this book, is one of the hottest topics in contemporary research. The book presents a critical appraisal of the new opportunities provided by nanotechnologies, and the nanotechnology-enabled advancements in the field of sensors. Being a new topic, information on nanosensors is scattered in research journals and reports. There is a paucity of books in this area. This book is intended to fill this long-felt need. Bringing together the widely spread information between the covers of an easy-to-read book will be helpful to all those working on nanosensors for instant reference and knowledge update'--
Includes bibliographical references and index.
Keywords: Nanostructured materials; Detectors